OPTIMALISASI PENGELOLAAN LINGKUNGAN DENGAN PENDEKATAN HOLISTIK KULTURAL - Saipul Bahri; Taufan Ratri Harjanto; Rosita Dwityaningsih; Ayu Pramita; Nurlinda Ayu Triwuri; Sheptia Whiting Hayati (Universitas Nahdlatul Ulama Sidoarjo, 2019)
The rapid population growth in Indonesia has an impact on increasing the amount of waste or household waste. Waste is the result of community activities so it should be instilled that waste management is a shared responsibility. According to the Central Statistics Agency of Indonesia, the amount of waste in 2020 in 384 cities in Indonesia will reach 80,235.87 tons every day. From the waste generated, it is estimated that 4.2% will be transported to the Final Disposal Site, 37.6% will be burned, disposed of into the river by 4.9% and untreated around 53.3%. One effort that has been made in Tambakreja Village, South Cilacap District, Cilacap Regency, Central Java through the use of household waste that is processed as compost to create a reduction in pollution to the environment. The waste or waste management program in Tambakreja Village RW 08 has been started since early 2014, namely processing waste in community settlements by launching a Waste Bank program called Bank Sampah Mandiri